The Effect Of Using Mind Mapping Method On Learning Motivation In Science Subject Of Fifth Grade At SD Inpres Sudiang Kota Makassar - Nurul Fadillah Hamka; Rohana Rohana; Muhammad Faisal (International Journal of Elementary School Teacher, 2021)
The research problem is low student learning motivation in science subjects in fifth grade of SD Inpres Sudiang Kota Makassar. The problem statement in this research there are: (1) how is the description of using mind mapping method in science subject?, (2) how is the description of students learning motivation in science subject?, (3) is there an effect of using mind mapping method on learning motivation in science subject at the fifth grade student of SD Inpres Sudiang Kota Makassar?. The purpose of this study there are: (1) to know the description of using mind mapping method in science subject, (2) to know the description of students learning motivation in science subject, (3) to know the effect of using mind mapping method on learning motivation in science subject at the fifth grade student of SD Inpres Sudiang Kota Makassar. The approach used in this study is quantitative the type of research is Quasi experiment. The focus of this research the used of the learning methods of Mind Mapping and student learning motivation. The population and sample of this study were fifth grade students of SD Inpres Sudiang Kota Makassar, with 60 students. Data collection techniques used were observation, questionnaire, and documentation. The technique of analyzing data used descriptive statistical and inferential statistical analysis. The results showed that there was: (1) The learning process was observed using the learning process sheet the results showed progress improvement in each meeting and categorized as very effective. (2) The learning motivation in experiment class more increased than in control class after giving treatment. (3) Mind mapping method had an effect on student learning motivation in science subject at the fifth grade student of SD Inpres Sudiang Kota Makassar.